Allantoin overaccumulation enhances production of metabolites under excess of metals but is not tightly regulated by nitric oxide - Dresler, Sławomir; Kováčik, Jozef; Sowa, Ireneusz; Wójciak, Magdalena; Strzemski, Maciej; Rysiak, Anna; Babula, Peter; Todd, Christopher D (Journal of hazardous materials, 2022)
The aln-3 mutant overaccumulating allantoin and respective wild type (WT) strain of Arabidopsis thaliana were exposed to cadmium (Cd) or mercury (Hg) with or without nitric oxide (NO) donor (sodium nitroprusside, SNP) to study cross-talk, metabolic and oxidative changes between these nitrogen sources (organic vs. inorganic). The aln-3 accumulated over 10-fold more allantoin than WT with the effect of Cd and Hg differing in leaf and root tissue: aln-3 contained more ascorbic acid and phytochelatins when treated with Cd or Hg and more Cd in both organs. SNP depleted leaf Cd and root Hg accumulation in aln3 but had a positive impact on the amount of metabolites typically in WT plants, indicating potentially negative relation between allantoin and NO. In agreement, aln-3 roots showed lower NO signals in control or metal treatments, but higher ROS signal, and SNP had more pronounced impact in WT roots. Flavonol glycosides were more abundant in aln-3 and were affected more by metals than by SNP. Malate was the most affected Krebs acid with strong reaction to SNP and Hg treatment. Data indicate that allantoin overaccumulation influences the accumulation of specific metabolites but nitric oxide has a greater impact on the metabolite profile in WT.
Keywords: Arabidopsis; Cadmium; Reactive oxygen species; kadmium; Plant Roots; Nitric Oxide Donors; Allantoin; Mercury; Nitric Oxide; Antioxidants; Flavonoids; Malic acid; oxid dusnatý; donory oxidu dusnatého; alantoin; kořeny rostlin; Ureides; rtuť